Kontroversi Awal Waktu Salat Subuh - Imanda, Iqmal (Cendekia Inovatif Dan Berbudaya, 2025)
The determination of the beginning of the Fajr (Subh) prayer time is a crucial issue in Islamic worship, as it directly affects the validity of both prayer and fasting. In Islamic law, the beginning of Subh is marked by the appearance of the true dawn (fajr ṣādiq), as stated in the Qur’an and Hadith. However, in practice, differences arise among religious authorities and astronomers regarding the sun’s position below the eastern horizon that signifies the fajr ṣādiq. In Indonesia, the Ministry of Religious Affairs adopts the -20° parameter, while many international institutions and contemporary Muslim astronomers use -18° to -15°, resulting in a time discrepancy of 10–30 minutes. This difference has triggered controversies in both astronomical and fiqh perspectives, raising doubts among Muslims about the validity of their worship. This article examines the scriptural basis of the Subh prayer time and the ongoing controversies surrounding it, emphasizing the need for synergy between hisab (astronomical calculation) and rukyat (direct observation), as well as the urgency of methodological updates for greater accuracy and contextual relevance. The study concludes that while the precautionary approach (iḥtiyāṭ) remains relevant, it should be complemented with scientific verification to ensure that the Subh prayer timetable is both religiously valid and astronomically reliable.